Incentivizing innovative entrepreneurship in quasi-markets: Theory and evidence from Sweden's schools and nursing homes - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2024)
Many countries have implemented quasi-markets to enhance entrepreneurship and innovation in welfare service provision. However, the benefits have generally been limited; this can also be observed in Sweden, a country which stands out for its extensive use of quasi-markets. Based on the Swedish experience, we contend that quasi-markets can unlock their innovation potential only under a suitable institutional framework. By analyzing the development of quasi-markets in schools and eldercare nursing homes, we demonstrate that competition and profit incentives, though crucial, are insufficient catalysts for innovation in quasi-market contexts. Such markets demand a set of supporting institutions of an epistemic nature. These institutions should enable users to make knowledgeable choices and motivate entrepreneurial providers to compete and innovate in ways that align with user preferences.
Keywords: H42; H44; H75; I22; I28; L88; O31; 330; Entrepreneurship; Innovation; Innovation Policy; Marketized care; Merit goods; Quasi-markets; Welfare services